Just-in-time production and delivery in supply chains: a hybrid evolutionary approach - Naso, D.; Surico, M.; Turchiano, B.; Kaymak, U. (2004 IEEE International Conference on Systems, Man and Cybernetics, 2004)
The timely production and distribution of rapidly perishable goods is one of the most challenging logistic problems in the context of supply chain operation. The problem involves several tightly interrelated planning, scheduling and routing problems, each with large combinatorial complexity. From a more practical perspective, the problem calls for a trade-off between risks and returns. To effectively deal with these considerable difficulties, we propose a novel meta-heuristic approach based on a hybrid evolutionary algorithm combined with constructive heuristics for addressing just-in-time production and delivery with time constraints on both the earliness and the lateness of supply. Distribution of ready-made concrete is used as a practical example. A case study based on industrial data illustrates the potential of the proposed approach.